Optimasi Kodon dan Konstruksi Plasmid Rekombinan Protein RBD SARS-CoV-2 pada E. coli BL21(DE3): Codon Optimization and Construction of Recombinant Plasmid for SARS-CoV-2 RBD Protein on E. coli BL21(DE3) - Purnamasari, Elly Widyarni Eka; Dini Wahyu Kartika Sari; Tenri Ashari Wanahari; Khairun Nissa; Kusumawati, Asmarani (Journal of Health (JoH), 2024)
Coronavirus Disease 2019 (COVID-19), caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) resulted over 7 million deaths worldwide. Comprehensive strategies are necessary to combat this pandemic, especially vaccination to mitigate further infection and devastation. The development of vaccines hinges upon the utilization of immunogenic proteins from the SARS-CoV-2 virus, with particular emphasis on the receptor-binding domain (RBD) located within the spike glycoprotein’s subunit 1. This protein plays a key role in the virus’s interaction with host cells via ACE2 receptor to infect the host along with the subunit 2 to mediate the cell membrane fusion. While there are multiple vaccines in existence, there is a requirement to create more affordable and accessible vaccine alternatives, especially in developing countries. Potential improvements can be implemented within the vaccine development paradigm, including the exploration of recombinant protein-based vaccines as a viable alternative. In the present study, we optimized the RBD gene sequence as the critical step to construct a recombinant plasmid for heterologous prokaryotic protein expression in Escherichia coli BL21(DE3). The optimized codon then inserted into the plasmid vector pET-15b and constructed a recombinant plasmid for transformation into cell host by heat-shock method. The study was evaluated and validated through colony PCR, plasmid isolation, and sequencing. These findings offering a foundational basis for further research in the expression and purification of RBD SARS-CoV-2 protein in E. coli BL21(DE3) as a candidate for subunit recombinant protein vaccine or diagnostic tool in COVID-19 research.